Respiration Status of Asthma Patients Who Get Nebulisation Using Jet Nebulizer Compared to Nebulizer Using Oxygen - Agus Santosa; Endiyono Endiyono (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Background: Some of regional hospitals still provide oxygen gas for nebulizer to therapies in astma patiens. The study was aimed to observe the effectiveness of jet nebulizer vs oxygen as a driving gas for nebulizer on respiratory parameters of asthma patients which is breath pattern, respiration rate (RR), breath sound, oxygen saturation (SpO2), peak expiratory flow rate (PEF. Method: The research was an experimental with a combination design, pre-post test with control group and post test only with control group in RSUD dr. R. Goeteng Taroenadibrata Purbalingga consisted of 60 respondents selected by proportional stratified random sampling. Data analysis used was independent t-test and fisher’r exact test. Result: There was no difference in the respiratory pattern variables between jet nebulizer and oxygen as a driving gas nebulizers (p> 0.05). The jet nebulizer was better in reducing RR in asthma patients than the oxygen as a driving gas nebulizer (p